Prevalence of corneal diseases in the rural Indian population: the Corneal Opacity Rural Epidemiological (CORE) study. Issue 2 (13th November 2014) - Gupta, Noopur; Vashist, Praveen; Tandon, Radhika; Gupta, Sanjeev K; Dwivedi, Sadanand; Mani, Kalaivani
Abstract : Objective: The present population-based study was undertaken to estimate the prevalence, determinants and causes of corneal morbidity and blindness in a rural North Indian population. Design: Population-based study in India with 12 899 participants of all ages. Methods: Participants were recruited from 25 village clusters of district Gurgaon, Haryana, India using random cluster sampling strategy. All individuals were examined in detail with a portable slit lamp for evidence of any corneal disease during the door-to-door examination. Comprehensive ocular examination including logMar visual acuity, slit lamp biomicroscopy, non-contact tonometry and dilated retinal evaluation was performed at a central clinic site in the respective villages. Results: Overall, 12 113 of 12 899 people (93.9% response rate) were examined during the household visits. Prevalence of corneal disease was 3.7% (95% CI 3.4% to 4.1%) and that of corneal blindness was 0.12% (95% CI 0.05% to 0.17%). Multivariable analysis demonstrated that corneal disease was significantly higher in the elderly (p<0.0001) and illiterates (p<0.0001). Common causes of corneal opacity in the study population were pterygium (34.5%), ocular trauma (22.3%) and infectious keratitis (14.9%). Corneal diseases contributing to blindness were post-surgical bullous keratopathy (46.2%) and corneal degenerations (23.1%). Conclusions: The study findings demonstrate that currently ocular trauma, infectious keratitis, post-surgical bullous keratopathy, and corneal degenerations are responsible for the major burden of corneal blindness and morbidity in the Indian population. The prevalence of corneal morbidity due to vitamin A deficiency and trachoma was low in this rural population.